REFLECT – A Teacher Training Program to Promote Gender Equality in Schools - Kollmayer, Marlene; Schultes, Marie-Therese; Lüftenegger, Marko; Finsterwald, Monika; Spiel, Christiane; Schober, Barbara (Frontiers in Education, 2020)
Despite formally equal educational opportunities for women and men, educational and occupational careers are still characterized by gender disparities rather than gender equality. Men are overrepresented in STEM fields and higher positions, while women are frequently working in low-status jobs in the health and social sector. These differences already emerge during school time, when girls report lower academic self-concepts in STEM subjects than boys even after achievement is controlled for while the same ist true for boys’ self-concepts in reading and languages. Gender stereotypes that are conveyed by socializing agents are assumed to play an important role in maintaining gender differences in education. Teachers are important starting points for promoting gender equality in education as their attitudes and instructional practices are known to influence students’ motivation and performance substantially. To promote girls and boys equally in coeducational settings, teachers have to reflect on their own gender stereotypes. Moreover, they require knowledge about gender differences in education and about teaching methods to foster the motivation of all students regardless of their gender. However, gender stereotypes are rarely dealt with in general teacher education and training programs that build teachers’ competences for reflective coeducation are sparse. Against this backdrop, we present the teacher training program REFLECT that was developed to foster secondary school teachers’ competences for supporting students in developing their individual potentials without being restricted by gender stereotypes. REFLECT is theoretically based on the systemic actiotope model and aims to expand teachers’ objective action repertoire (knowledge, teaching methods) as well as their subjective action space (self-efficacy beliefs, implicit theories). The results of a pilot study show the effectiveness of REFLECT. Teachers’ objective action repertoire and subjective action space for promoting boys and girls equally increased, as did students’ knowledge of gender differences and perception of diversity fairness in the classroom. Implementing the contents of REFLECT in general teacher education could contribute to sustainably achieving gender equality in education.